It's quantum! - George Kahale (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
Quantum garners the least attention in ISDS, but it is where the money is. Mega-claims have become commonplace, increasingly leading to mega-awards that would have been unthinkable only a decade ago. The author explores these developments from the perspective of a practitioner defending against mega-claims.
Keywords: 330